Finite Element Analysis of Composite Beam with Shear Connectors. (2016) - Anju, T.; Smitha, K.K.
Abstract: Composite structures consisting of concrete slab and rolled up steel sections are widely used structural members in bridges and high rise buildings. The composite action is established by connecting the concrete slab and the steel section by using shear connectors. In this paper, four different types of shear connectors have been analyzed and the best connector for a particular composite beam has been evaluated based on its performance under static load keeping the loading and the amount of steel in the connector as a common aspect.